1998
DOI: 10.1111/j.1528-1157.1998.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Cardiovascular Autonomic Responses in Patients with Epilepsy

Abstract: Summary: Purpose: To evaluate the interictal autonomic nervous system function in 84 patients with epilepsy: 37 with newly diagnosed, previously untreated epilepsy, and 47 patients receiving long-term carbamazepine (CBZ), phenytoin (PHT), or valproate (VPA) monotherapy, or CBZ plus PHT, or CBZ plus VPA for their seizure disorder. Methods:We assessed autonomic control of the cardiovascular regulatory system.by standardized cardiovascular reflex tests measuring changes in heart rate (HR) and blood pressure (BP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 32 publications
(22 reference statements)
4
64
2
4
Order By: Relevance
“…Changes in HRV vary between seizure types; for example in temporal lobe seizures, increased sympathetic and decreased vagal heart rate modulation often precedes ictal electroencephalographic (EEG) changes (27)(28)(29). Previous studies have reported diminished interictal HRV in temporal lobe epileptic patients using conventional short and long-term electrocardiogram (ECG) recordings, but general study with focused on changes in heart rate during pre-ictal phase failed, and many aspects of it has remained unclear (25,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in HRV vary between seizure types; for example in temporal lobe seizures, increased sympathetic and decreased vagal heart rate modulation often precedes ictal electroencephalographic (EEG) changes (27)(28)(29). Previous studies have reported diminished interictal HRV in temporal lobe epileptic patients using conventional short and long-term electrocardiogram (ECG) recordings, but general study with focused on changes in heart rate during pre-ictal phase failed, and many aspects of it has remained unclear (25,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in blood pressure and heart rate during orthostasis and cold pressor test are significantly higher in patients with partial epilepsy than in control subjects (20)(21)(22). In patients with temporal lobe epilepsy, measurement of heart-rate Hand grip was defined as an increase over the diastolic 11 mmHg Hand grip was defined as an increase, at least in two of systolic, diastolic blood pressure or heart rate Increase in both SBP and DBP parameters more than 20 mmHg Increase in one parameter of SBP or DBP No obvious change in parameters *-p value< 0.05 is considered significant variability from short-term ECG recordings showed cardiovascular dysregulation (20)(21)(22). In these patients, not only heart rate is variability reduced, but also is long-term fractal organization, and complexity of heart rate dynamics is apparently altered (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced heart rate responses to Valsalva maneuver were noted in patients receiving benzodiazepine agents as monotherapy and in patients receiving benzodiazepine agents during deep breathing (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined the Valsalva ratio as the ratio of the longest RRinterval during the first 20 s after blowing into a mouthpiece at a pressure of 40 mm Hg with the glottis open for 15 s to the shortest RR-interval during the strain [17].…”
Section: Autonomic Function Testingmentioning
confidence: 99%